Fitness Cost and Competitive Ability to Different Ploidy Levels in Ryegrass Genotypes - SCHMITZ,M.F. (2019)
ABSTRACT: The intergenotypic competition of tetraploid ryegrass with natural diploid population may be a tool to reduce the frequency of resistant individuals in an area. This study aimed to identify and compare the phenological development, fitness cost, and competitive ability between diploid and tetraploid ryegrass genotypes. Genotypes were grown in pots, and the morphological variables of genotype growth were assessed every 15 days up to 120 days after emergence to evaluate the fitness cost. Phenological development and seed yield components were measured in a single time together with the fitness cost. Competitive ability was determined in a replacement-series experiment with proportions of tetraploid and diploid ryegrass, in which the number of tillers, plant height, leaf area, and shoot dry weight were assessed at 50 days after emergence. The results of fitness cost showed that the number of tillers, leaf area, root dry weight, and the number of seeds were higher for tetraploid ryegrass, which presented a higher competitive ability than the diploid genotype regardless of the tested proportions. Tetraploid ryegrass may be useful for reducing the frequency of herbicide-resistant diploid ryegrass because of its higher competitive potential.